Simultaneous detection of multiple foodborne bacteria by loop-mediated isothermal amplification on a microfluidic chip through colorimetric and fluorescent assay. (April 2022) - Cao, Yanan; Ye, Cheng; Zhang, Cong; Zhang, Guohao; Hu, Haiming; Zhang, Zhigang; Fang, Haitian; Zheng, Junping; Liu, Hongtao
Abstract: The integration of loop-mediated isothermal amplification (LAMP) onto a microfluidic chip adds more simplicity and portability for food safety control. However, this system for multiple-target detection was less used on foodborne bacteria. Here, we utilized a ten-well microfluidic chip with pre-loaded LAMP primer sets for the quantitative and qualitative detection of Salmonella, Staphylococcus aureus, Escherichia coli O157:H7, and Shigella . The specificity and sensitivity of designed primers targeting sirA, spA, fliC, and ipaH genes were validated. Using regular tubes and the ten-well microfluidic chips, these four pathogens could be simultaneously detected within 45 min by LAMP with fluorescent and colorimetric readouts, respectively. Finally, the results demonstrated that the limit of detection reached 8 × 10 3  CFU mL −1 genomic DNA with a recovery rate of 86.1%∼110%. In summary, our microfluidic chip platform displayed obvious advantages in time-saving, cost-effectiveness, and sensitivity, which is applicable for in-field monitoring of food pathogens. Graphical abstract: Image 1 Highlights: ● LAMP reaction is integrated on a 10-well microfluidic chip for food detection. ● The microfluidic chip is used for both quantitative and qualitative detection. ● The fluorescent intensity and colorimetric amplification readouts can be obtained. ● This microfluidic chip platform simultaneously detects four bacteria within 45 min.